STRUKTUR KOMUNITAS MIKROBA TANAH DAN IMPLIKASINYA DALAM MEWUJUDKAN SISTEM PERTANIAN BERKELANJUTAN - Prihastuti, Prihastuti (El-Hayah : Jurnal Biologi, 2011)
Soils are made up of organic and an organic material. The organic soil component contains all the living creatures in the soil and the dead ones in various stages of decomposition.Â  Biological activity in soil helps to recycle nutrients, decompose organic matter making nutrient available for plant uptake, stabilize humus, and form soil particles.The extent of the diversity of microbial in soil is seen to be critical to the maintenance of soil health and quality, as a wide range of microbial is involved in important soil functions.Â  That ecologically managed soils have a greater quantity and diversity of soil microbial. The two main drivers of soil microbial community structure, i.e., plant type and soil type, are thought to exert their function in a complex manner. The fact that in some situations the soil and in others the plant type is the key factor determining soil microbial diversity is related to their complexity of the microbial interactions in soil, including interactions between microbial and soil and microbial and plants. The basic premise of organic soil stewardship is that all plant nutrients are present in the soil by maintaining a biologically active soil environment. The diversity of microbial communities has on ecological function and resilience to disturbances in soil ecosystems. Relationships are often observed between the extent of microbial diversity in soil, soil and plant quality and ecosystem sustainability. Agricultural management can be directed toward maximizing the quality of the soil microbial community in terms of disease suppression, if it is possible to shift soil microbial communities.Keywords: structure, microbial, implication, sustainable agriculture